1985
DOI: 10.1177/019459988509300217
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Perforations of the Tympanic Membrane: Early Closure with Paper Tape Patching

Abstract: There is a difference of opinion about treating traumatic perforations of the tympanic membrane expectantly or with early surgery. Those who treat expectantly argue that most of the perforations will heal, given enough time. Those who argue for early closure note the occasional finding of middle ear damage, high closure rates, and faster healing. We present 50 consecutive traumatic perforations seen over a 3-year period and initially treated with paper tape patches (3M Micropore) applied in the office under lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
1
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 7 publications
4
53
1
1
Order By: Relevance
“…The eardrum flap and curling direction did not affect the effect of patching. These findings of our study are quite in accordance with the reports of Camnitz and Bost [9] .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The eardrum flap and curling direction did not affect the effect of patching. These findings of our study are quite in accordance with the reports of Camnitz and Bost [9] .…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, with the intention of repairing the eardrum flap, the following steps were conducted in the surgical procedure: the perforated edge was aligned with an angle needle; the perforation area was reduced and the eardrum flap was fixed with a patch to ensure that the epidermal cells grew along the same plane. This would lead to shortening of the perforation closure time [6][7][8][9] , but, as far as we know, there exist few observations of eardrum flap dynamics while exploring the healing of traumatic perforations of human tympanic membranes. In most clinical researches conducted on this subject, the closure rate and closure time of tympanic membrane perforations are deduced by the conclusions obtained after treating the patients for a duration of at least 1 week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly due to prevalence of domestic violence and child abuse in our society. Lindeman et al 14 and Berger et al 15 also reported higher incidence of traumatic TM perforation amongst young females as in our series while Camintz et al 16 reported high prevalence in males. The most common side affected was the left side (51.7%) in our series while right ear was injured in 32.8% of cases and bilateral involvement was seen in 15.5 % of cases.…”
Section: Discussionsupporting
confidence: 69%
“…Present methods of tympanic membrane repair may include simple measures such as paper patching, which often fails to close large, chronic perforations [2], The paper patch method has a 10-94% closure rate, with the best results obtained for small, acute traumatic perfora tions [2][3][4], Due to the high spontaneous closure rate of acute tympanic perforations, several studies have shown no statistical difference between the paper patch method and spontaneous healing, raising doubt concerning the utility of paper patching in this setting [ 1,[3][4][5][6], For larger defects, perforations may require complex repair tech niques which involve highly experienced otologic skills, an operating room setting, and specialized equipment. In microsurgical grafting with fascia, results have been re ported ranging from 79 to >90%, with the success rates dropping to 57-81 % in larger perforations involving more than 50% of the tympanic membrane [7,8],…”
Section: Introductionmentioning
confidence: 99%